Balance exercise education and training as an effort to prevent fall risk among older adults in the Al-Wahab religious study group Air Paoh Village - Lisdahayati Lisdahayati; Saprianto Saprianto; Umar Hasan Martadinata; D Eka Harsanto (Science Center Group, 2026)
Background: Falls are a major safety problem among older adults because aging is associated with decreased muscle strength, postural control, and body stability. Older adults in the Al-Wahab religious study group had limited exposure to information on fall prevention and had no structured balance exercise program. Objective: This community service program aimed to improve older adults’ knowledge and skills in performing balance exercises as an effort to prevent fall risk. Methods: This program used educational, participatory, and applicative approaches. The activity involved 25 older adults who met the participant criteria, including older age, ability to walk independently or with minimal assistance, adequate communication and cognitive ability, willingness to participate, and no acute medical condition that limited safe exercise. The program consisted of interactive education, group discussion, demonstration, redemonstration of balance exercises, and distribution of educational media. Evaluation was conducted using pre-test and post-test knowledge questionnaires and observation of participants’ exercise skills. Results: Before the program, 20 participants (80%) had poor knowledge and 5 participants (20%) had good knowledge. After the program, 21 participants (84%) had good knowledge and 4 participants (16%) still had poor knowledge. Participants were able to practice basic balance movements with guidance, and family members or religious group cadres were involved to support home-based practice. Conclusion: Balance exercise education supported by demonstration and educational media improved older adults’ knowledge and practical skills in fall-risk prevention. Continuous practice with support from community cadres and primary health care services is recommended.